Business and professional development (Effective presentations series)
In Effective Presentation: Planning a Presentation, you will learn how to determine realistic presentation objectives, how to analyze your audience, and how to use supporting materials effectively. In addition, you will learn how to organize your presentation clearly and successfully incorporate visual aids into your presentation.